Linking animal behavior to ecosystem change in disturbed environments - Rahman, Tawfiqur; Candolin, Ulrika (Frontiers in Ecology and Evolution, 2022)
Environmental disturbances often cause individuals to change their behaviour. The behavioural responses can induce a chain of reactions through the network of species interactions, via consumptive and trait mediated connections. Given that species interactions define ecosystem structure and functioning, changes to these interactions often have ecological repercussions. Here, we explore the transmission of behavioural responses through the network of species interactions, and how the responses influence ecological conditions. We describe the underlying mechanisms and the ultimate impact that the behavioural responses can have on ecosystem structure and functioning, including biodiversity and ecosystems stability and services. We explain why behavioural responses of some species have a larger impact than that of others on ecosystems, and why research should focus on these species and their interactions. With the work, we synthesise existing theory and empirical evidence to provide a conceptual framework that links behaviour responses to altered species interactions, community dynamics, and ecosystem processes. Considering that species interactions link biodiversity to ecosystem functioning, a deeper understanding of behavioural responses and their causes and consequences can improve our knowledge of the mechanisms and pathways through which human activities alter ecosystems. This knowledge can improve our ability to predict the effects of ongoing disturbances on communities and ecosystems and decide on the interventions needed to mitigate negative effects.